Pengaruh Gender Dan Muatan Etika Dalam Pengajaran Akuntansi Keuangan Pada Persepsi Etika Mahasiswa - Andina Ayu Triani (Ultima Accounting : Jurnal Ilmu Akuntansi, 2011)
This research is an experimental research which is conducted to examine the effect of gender and ethics toward ethical perceptions for accounting students. The objects of this research were students who were taking intermediate accounting class at Multimedia Nusantara University and Bakrie University. For the data analysis techniques, validity of data was analyzed by using Confirmatory Factor test analysis (CFA), the reliability test data was analyzed by using the Cronbach Alpha Coefficient (α), and hypothesis tests was analyzed by using simple regression (Simple Regression). All of the data used in this research are valid and reliable. The classical assumption test was done before the hypothesis test was analyzed. From the results of hypothesis testing, Ha1 was rejected which means that gender variables cannot be used to predict the perception of ethics and Ha2 was rejected which means that charges of ethics cannot be used to predict the perception of ethics. Keywords: gender, ethics, perception of ethics